Shakespeare and popular music - Hansen, Adam (Continuum, 2010)
How have Shakespearean characters, words, texts and iconography been represented and reworked through popular music? Do all types of popular music represent Shakespeare in the same ways? And how do the links between Shakespeare and popular music challenge what we think we know about both Shakespeare and popular music? One of the enduring myths about how Shakespeare and popular music relate is that they don't - after all the antagonism between high culture and pop music could be considered mutual. In the first book of its kind, Adam Hansen shows what happens to Shakespeare when he exists in and.